2015
DOI: 10.1118/1.4908207
|View full text |Cite
|
Sign up to set email alerts
|

Initial implementation of the conversion from the energy‐subtracted CT number to electron density in tissue inhomogeneity corrections: An anthropomorphic phantom study of radiotherapy treatment planning

Abstract: The ΔHU-ρ(e) conversion can be implemented for currently available TPS's without any modifications or extensions. The ΔHU-ρ(e) conversion appears to be a promising method for providing an accurate and reliable inhomogeneity correction in treatment planning for any ill-conditioned scans that include (i) the use of a calibration EDP that is nonequivalent to the patient's body tissues, (ii) a mismatch between the size of the patient and the calibration EDP, or (iii) a large quantity of high-density and high-atomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 33 publications
0
27
0
Order By: Relevance
“…Though  dual-energy CT imaging may not be as successful as a dedicated artifact reduction algorithm, such as - or , dual-energy CT nonetheless has many applications in radiation therapy aside from metal artifact reduction and still has the potential to improve the accuracy of treatments in other ways. 10,32,33 In summary, our results indicate that of the three methods investigated, - is the safest option for all-purpose metal artifact reduction in CT simulation imaging.  showed the greatest potential, but had serious limitations.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Though  dual-energy CT imaging may not be as successful as a dedicated artifact reduction algorithm, such as - or , dual-energy CT nonetheless has many applications in radiation therapy aside from metal artifact reduction and still has the potential to improve the accuracy of treatments in other ways. 10,32,33 In summary, our results indicate that of the three methods investigated, - is the safest option for all-purpose metal artifact reduction in CT simulation imaging.  showed the greatest potential, but had serious limitations.…”
Section: Discussionmentioning
confidence: 62%
“…5 Another approach to metal artifact reduction is the use of dual-energy CT. Dual-energy CT has many applications for diagnostic imaging, [6][7][8] but few studies have looked at its use for treatment planning. [9][10][11] One such dual-energy CT system, GE Healthcare's Discovery CT750 HD (Milwaukee, WI), acquires dual-energy projection data via fast kilovoltage switching with a single x-ray source. This dual-energy projection data can then be reconstructed to generate virtual monochromatic images at various energy levels (from 40 to 140 keV), called gemstone spectral imaging ().…”
Section: Introductionmentioning
confidence: 99%
“…Saito et al recently reported that for MV photon therapy, DECT is more robust to variations in object size than SECT. 10 Imaging artifacts may also affect SECT and DECT differently and it may be interesting to compare their impact.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9] However, investigation of clinical external beam treatment planning (TP) on DECT images has been restricted to megavoltage photons using anthropomorphic phantoms. 10 To our knowledge, no study of proton therapy treatment planning on dual energy CT images of patients exists in the peer reviewed literature.…”
Section: Introductionmentioning
confidence: 99%
“…for Z eff calculation. Saito and his collaborators demonstrated in previous studies that ρ e can be computed by merely performing the weighted subtraction of high‐ and low‐energy CT images using a calibration phantom and a least‐squares fitting procedure to find the optimal weighting factor. This method yielded values of ρ e with an absolute error of less than 1% for calibration phantoms.…”
Section: Introductionmentioning
confidence: 99%